2021
DOI: 10.46717/igj.54.2a.1ms-2021-07-22
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Characteristics of Mud Diapir in Song Hong Basin, Offshore Vietnam

Abstract: Seismic characteristics of mud diapir has been investigate over an area of 3900 km2, located in the central part of Song Hong basin, using four 2D seismic lines. There are six mud diapirs and three mud pipes have been documented. The core of the diapir is characterized as a zone of chaotic, disrupted seismic reflection, with the amplitude reflection ranging from low the high. High amplitude reflections are distributed in the top of the some diapir, which is possibly related to the gas accumulation. They are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Generally, frequency attributes relate to bed thickness, wave scattering, and absorption. Time attributes relate to structure and amplitude attributes relate to stratigraphy (Le and Ha, 2020).…”
Section: Seismic Facies and Seismic Attribute Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, frequency attributes relate to bed thickness, wave scattering, and absorption. Time attributes relate to structure and amplitude attributes relate to stratigraphy (Le and Ha, 2020).…”
Section: Seismic Facies and Seismic Attribute Analysismentioning
confidence: 99%
“…For example, Nguyen et al (2019) showed limited conditions of the number of drilled wells in the Phu Khanh basin, the application of ANN has been effective when integrating the results of analysis of seismic data, well-logs, core analysis to predict the distribution and quality of potential reservoir in the basin. In the Song Hong basin, Le and Ha (2020) used ANN to integrate 2D seismic attributes to identify mud diapirs and hydrocarbon traps. Tran et al (2020) used ANN to predict the distribution of volcanic materials in Cuu Long basin.…”
Section: Introductionmentioning
confidence: 99%